Ocular surface lubricants. Issue 5 (October 2017) - Bielory, Leonard; Wagle, Preeti
Abstract : Purpose of review: The purpose of this article is to provide an overview of the ocular lubricants currently available, consider the components of the various formulations and highlight the status of preservative use in the treatment of anterior ocular surface diseases. Recent findings: The primary components of ocular surface lubrication have been, in the past, based on various cellulose formulations that increase hydration. Advances in lubrication have come from areas of the human body requiring lubrication such as the skeletal joints as well as examining the use of natural components of the tear fluid. These have resulted in novel modifications of existing tear components, for example, thiolated carboxymethyl hyaluronic acid which creates crosslinking to mechanically increase retention time for ocular surface hydration. Other proteoglycans such as lubricin, having one of the lowest coefficients of friction in nature, to a lipopolysaccharide derivative of tamarind seed, may provide a unique delivery system for lubricants and medications. Summary: The present state of ocular surface lubrication is slowly advancing from the routine use of cellulose-based solutions and gels to more advanced replacement with natural tear components. The advances that are occurring on other lubricating surfaces of the musculoskeletal system are also providing some insights into potential use on the ocular surface.